Real Convergence, Steps from Adherence to Integration - Mihail Busu; Adina Gyorgy (Amfiteatru Economic Journal, 2016)
The macroeconomic model Solow-Swan shows that the marginal rates of capital, technology and labor force, with positive values, have the capacity to stimulate the economic growth of the emergent economies, as in the case of Romania, for the 2005-2014 period, facilitating the determination of specific correlations between macroeconomic indicators to analyze the convergence towards the average European Union (EU). The economic theory, highlighted in particular by the Solow-Swan model, was applied in the current paper, to determine the potential of real convergence. Moreover, the statistics for the period 2005-2014 facilitated the analysis of the growth and recession factors specific to economies of Central and Eastern Europe and placed Romania amongst the EU countries with emergent economies and potential of economic growth. The European Commission's reports regarding the macroeconomic imbalance procedure draw attention on the same indicators presented in the article to address proper recommendations and support corrective measures. Making a step from nominal to real convergence, the latter derives naturally from the need to recoup the gaps in comparison with developed economies amongst countries of the Euro Area.
Keywords: O18; O31; L84; 330; economic growth; emergent economies integration; real convergence; macroeconomic model